STRATEGI PENGEMBANGAN WISATA DI DESA GUNUNG SEMBILAN KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Fitri Ramadhani; Sri Buwono; Putri Tipa Anasi (Universitas Tanjungpura, 2021)
AbstractThis study aims to identify and determine development strategies that can be carried out on tourism potential in Gunung Sembilan Village. This research is a descriptive type of research with a qualitative research form. Sources of research data on tourism development strategies in Gunung Sembilan Village are in the form of documents, archives, and other records that strengthen the picture of the situation through visual language. Data collection techniques are observation and interviews. The results of this study are (1) the distribution of potential and identification of tourism potential, both natural tourism and cultural tourism in Gunung Sembilan Village (2) The condition of tourism potential in terms of accessibility is good. This is because the distance between one potential and another is close, but there are still some access roads that are still not good to use or pass. (3) The strategy that can be done is the SO strategy, which is to take advantage of existing opportunities and then add various supporting facilities and various additional attractions to attract tourists. Community involvement is very necessary so that this strategy can run well and make the development carried out run smoothly.Keyword: identification, strategy, tourism potential